2010
DOI: 10.5424/fs/2010193-9097
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity is stronger than adaptative differentiation among Mediterranean stone pine provenances

Abstract: The Mediterranean stone pine, Pinus pinea L., seems to be well adapted to the different climate zones of its distribution range that spans four thousand kilometres along the Northern shore of the Mediterranean Sea. But recent molecular studies revealed it to be extremely genetically depauperate for a widespread tree. In this context, a provenances trial should elucidate whether any differentiation in adaptative traits can be identified between 34 accessions covering its natural range. The presence of strong sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
(42 reference statements)
2
17
0
3
Order By: Relevance
“…In this study, the tree height reached at 19 years after planting showed statistically significant differences among provenances, as previously reported in several studies (Gordo et al 2007, Mutke et al 2010, Carrasquihno & Gonçalves 2013. The best performance of Spanish provenances in terms of DBH and crown diameter could be explained by the more arid conditions in their area of origin compared with those of the other provenances, allowing a better adaptation of the Spanish provenances to the conditions of the trial site in Casablanca.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the tree height reached at 19 years after planting showed statistically significant differences among provenances, as previously reported in several studies (Gordo et al 2007, Mutke et al 2010, Carrasquihno & Gonçalves 2013. The best performance of Spanish provenances in terms of DBH and crown diameter could be explained by the more arid conditions in their area of origin compared with those of the other provenances, allowing a better adaptation of the Spanish provenances to the conditions of the trial site in Casablanca.…”
Section: Discussionsupporting
confidence: 84%
“…However, this is a widespread species that grows under diverse environmental conditions, indicating that genetic variability does not entirely explain its adaptability (Vendramin et al, 2008;Soto et al, 2010). In fact, the successful adaptation of P. pinea seems to depend largely on the variability of phenotypic traits, which is high in this species (Mutke et al, 2010(Mutke et al, , 2013Sánchez-Gómez et al, 2011;Sáez-Laguna et al, 2014). Thus, phenotypic plasticity may explain the observed variability of the growth response to climate in different regions, that could suggest the capacity of P. pinea to adapt the annual distribution of cambial activity depending on site-specific climatic conditions.…”
Section: Spatiotemporal Variability Of Growth-climate Relationshipsmentioning
confidence: 99%
“…Sin embargo, incluso en la Península Ibérica, donde la variación genética de P. halepensis es menor debido a la historia de migración de la especie ), la diferenciación entre procedencias también está presente (Tabla 2). Así, salvo casos excepcionales como P. pinea (MUTKE et al 2010), la variación intraespecífica es un hallazgo común. Este hecho pone de manifiesto la relevancia de los datos obtenidos en ensayos de ambiente común para caracterizar los materiales de base de cara a la gestión forestal sostenible.…”
Section: Discussionunclassified
“…So, barring some exceptional cases like P. pinea (Mutke et al, 2010), within-species variation is a frequent finding (Alberto et al, 2013).…”
Section: Population Differentiation and Local Adaptationmentioning
confidence: 99%